Nigeria Since independence The First 25 Years - Tamuno N. Tekena; Atanda J. A. (Nigeria Heinmann Educational Books, 1989)
This is volume 3 of the publication "Nigeria since independence the first 25 years" by the panel on Nigeria Since independence History Project. This volume focus on developments in the educational sector.
uaa 23/01/19
Loans.
Keywords: History; Eduction; Nigeria